SYNTHESIS OF CIS-1-AMINO-3-HYDROXYMETHYL-CYCLOBUTANE-1-CARBOXYLIC AND TRANS-1-AMINO-3-HYDROXYMETHYL-CYCLOBUTANE-1-CARBOXYLIC ACIDS - Fleet, G; Seijas, J; Tato, M (1988)
The stereospecific syntheses of cis- and trans-1-amino-3-hydroxymethyl-cyclobutane-1-carboxylic acids from 3-oxabicyclo[3.1.1] heptan-2-one-1-carboxylic acid are described. © 1988.